Lucky for good - Patron, Susan, 1948-; McGuire, Erin (New York : Atheneum Books for Young Readers, 2011)
Eleven-year-old Lucky feels like the universe is conspiring against her as she faces troubles with her father, the health inspector, her school principal, and middle school boys.
Booklist starred
Horn Book
School Library Journal
Booklist starred, June 2011
Bulletin (Center for Children's books), July 2011
Horn Book, July 2011
Keywords: Christian life -- Juvenile fiction; Community life -- California -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Restaurants -- Juvenile fiction; Christian life -- Fiction; Community life -- California -- Fiction; Interpersonal relations -- Fiction; Mothers and sons -- Fiction; Restaurants -- Fiction; Christian life -- Fiction; Community life -- California -- Fiction; Interpersonal relations -- Fiction; Mother-son relationship -- Fiction; Restaurants -- Fiction; California -- Juvenile fiction; California -- Fiction; California -- Fiction